Selfies and the (Creative) Self: A Diary Study - Karwowski, Maciej; Brzeski, Arkadiusz (Frontiers in Psychology, 2017)
In this diary investigation, over two weeks we monitored the intensity of selfie posting among 292 Facebook users (60% females), aged between 18 and 50, to estimate the extent of selfying’s day-to-day variability and its predictors. The obtained effect was large; 64% of the variability in selfying was located within rather than between individuals. Day-to-day changes in creative activity explained a significant proportion of selfying, similarly as previous creative achievement did. At the same time, intelligence was negatively linked to the intensity of selfie posting and moderated the relationship between creative achievements and selfying. We discuss hypothetical links between selfie posting and the situational and individual differences characteristics related to creativity and cognitive abilities.